Priorities for public investment in agriculture and rural areas (GRP 3) - Renkow, Mitch (International Food Policy Research Institute, 2011)
Public investment in agriculture and rural infrastructure is an important driver of agricultural growth and has a significant bearing on poverty outcomes. Determining the right levels and types of investments requires that policymakers have reliable and context-specific information about the impacts of different types of public investments. The International Food Policy Research Institute (IFPRI) initiated its Global Research Program on Priorities for Public Investment in Agriculture and Rural Areas (GRP-3) in 1998 to provide such information.